In Search of Pre-Service EFL Certificate Teachers' Attitudes towards Technology - Yuksel, Gulru; Kavanoz, Suzan (ELSEVIER SCIENCE BV, 2011)
The increasing importance of computers in today's world forces teachers and educators to become technology-proficient teachers, and to make use of technology in the classroom practices. All over the world most countries acknowledging the need for technologically proficient teachers, have started to infuse some degree of technological competency into pre-service teacher training programmes. Turkey was not an exception. The Turkish Ministry of National Education (MoNE) has started to promote computer use within schools, through policy, and through the provision of computers and professional development (Akkoyunlu, 2002; Rosaen, Hobson, & Khan, 2003; Cohen & Tally, 2004). The Council of Higher Education (HEC) has responded to these initiatives by integrating technology into teacher education programmes. However, like in many other countries several problems have been encountered in the implementation of technology (Salaberry, 2001; Asan, 2003; Cakiroglu & Cakiroglu, 2003; zden, 2007). Among several other problems prospective teachers' attitudes towards technology is the most important one (Gunter, 2001; Johnson & Howell, 2005). Given the significance this study investigated the attitudes of pre-service TEFL teachers toward technology. A twelve item 5-point Likert scale questionnaire was used to collect data from a sample of 200 TEFL Certificate programme students in a state university in Istanbul. Additionally, the study investigated the relationship between attitudes and two independent variables: academic background and gender. The study will contribute to the knowledge regarding the importance of pre-service EFL teachers' attitudes towards the use of technology for the purpose of teaching a foreign language. (C) 2010 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the Guest Editor.
Keywords: pre-service EFL teachers; attitudes; technology use; gender; certificate program; Computer Science; Engineering